Enhanced NCLX-dependent mitochondrial Ca2+ efflux attenuates pathological remodeling in heart failure. (June 2022) - Garbincius, Joanne F.; Luongo, Timothy S.; Jadiya, Pooja; Hildebrand, Alycia N.; Kolmetzky, Devin W.; Mangold, Adam S.; Roy, Rajika; Ibetti, Jessica; Nwokedi, Mary; Koch, Walter J.; Elrod, John W.
Abstract: Mitochondrial calcium (m Ca 2+ ) uptake couples changes in cardiomyocyte energetic demand to mitochondrial ATP production. However, excessive m Ca 2+ uptake triggers permeability transition and necrosis. Despite these established roles during acute stress, the involvement of m Ca 2+ signaling in cardiac adaptations to chronic stress remains poorly defined. Changes in NCLX expression are reported in heart failure (HF) patients and models of cardiac hypertrophy. Therefore, we hypothesized that altered m Ca 2+ homeostasis contributes to the hypertrophic remodeling of the myocardium that occurs upon a sustained increase in cardiac workload. The impact of m Ca 2+ flux on cardiac function and remodeling was examined by subjecting mice with cardiomyocyte-specific overexpression (OE) of the mitochondrial Na + /Ca 2+ exchanger (NCLX), the primary mediator of m Ca 2+ efflux, to several well-established models of hypertrophic and non-ischemic HF. Cardiomyocyte NCLX-OE preserved contractile function, prevented hypertrophy and fibrosis, and attenuated maladaptive gene programs in mice subjected to chronic pressure overload. Hypertrophy was attenuated in NCLX-OE mice, prior to any decline in cardiac contractility. NCLX-OE similarly attenuated deleterious cardiac remodeling in mice subjected to chronic neurohormonal stimulation. However, cardiomyocyte NCLX-OE unexpectedly reduced overall survival in mice subjected to severe neurohormonal stress with angiotensin II + phenylephrine. Adenoviral NCLX expression limited m Ca 2+ accumulation, oxidative metabolism, and de novo protein synthesis during hypertrophic stimulation of cardiomyocytes in vitro. Our findings provide genetic evidence for the contribution of m Ca 2+ to early pathological remodeling in non-ischemic heart disease, but also highlight a deleterious consequence of increasing m Ca 2+ efflux when the heart is subjected to extreme, sustained neurohormonal stress. Graphical abstract: Unlabelled Image Highlights: The mitochondrial Na + /Ca 2+ exchanger, NCLX, mediates mitochondrial calcium efflux. NCLX limits mitochondrial Ca 2+ accumulation upon hypertrophic stimulation. NCLX limits oxidative metabolism and protein synthesis during hypertrophy. NCLX overexpression attenuates pathological cardiac hypertrophy in vivo.